LEVEL OF PHYSICAL ACTIVITY AND NUTRITIONAL STATUS OF STUDENTS AT A PUBLIC UNIVERSITY IN BRAZIL (Fiep Bulletin - online, 2013)
Physical activity is an essential component for acquiring and maintaining a good quality of life. Excess body fat and physical inactivity are highly prevalent risk factors for cardiovascular disease. The aim of this study was to assess the level of physical activity and nutritional status of students at a public federal university in Brazil. The sample, probabilistically proportional, was made up of 642 students (46.67% male and 53.33% females), with an average age of 21.99 ± 4.07 years. The method used to measure the level of physical activity was the International Physical Activity Questionnaire (IPAQ), in its shortened version. The nutritional status was classified by body mass index (BMI) and central adiposity by waist circumference. As for the levels of physical activity, it was observed that 25.3% of students were classified as insufficiently active and 27.5% as sedentary. The largest proportion of sedentary students was found at the Center for Science Education (40.78%). The average time devoted to the use of electronics was 2.56 hours per day. Excess weight (BMI = 25) was found in 19.03% (n = 126) of students, and the proportion of overweight and obese students was 15.10% and 3.92% respectively, with 24.77% (n = 28) of them physically inactive. The prevalence of overweight males was highest at the Center of Natural Sciences and for female was highest at the Center for Human Sciences and Languages (p 0.05). Considering the high proportion of students classified as sedentary or insufficiently active, strategic interventions are needed to promote a more active lifestyle among university students.
Keywords: Physical activity; sedentarism; obesity; students